Impact of Incentive Management Strategies on Employee Performance among Telecommunication Firms in Kaduna Metroplis - Gadi, Paul; Bagobiri, Esther Yimi (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The study examined the impact of incentive management strategies on employee performance among telecommunication firms in Ka-duna metropolis. The objectives of the study were to determine the impacts of monetary incentive management strategies and non-mon-etary incentive management strategies on employee performance among telecommunication firms in Kaduna metropolis. The study employed survey design method in which a specially designed ques-tionnaire was used to collect primary data from respondents in the study. The target population of the study was employees from the head branches of four selected telecommunication firms in Kaduna metropolis; providing network reception service for calls and inter-net access data to residence in Kaduna metropolis. The firms include MTN, Airtel, 9Mobile and Glo. The population of employees in these firms’ head branches were; 66 in MTN, 49 in Airtel, 61 in 9Mobile and 54 in Glo; making a total of 230. The sample of the study was same as that of the population, as census sampling technique was used to de-cide the sample size. Self-administered questionnaire was designed and used to collect the primary data of the study. The collected data for the study was analysed using descriptive statistical analysis tools (mean scores and standard deviation) to summarize the responses and inferential statistical tool (Regression model) to determine whether incentive management strategies have impact on employee performance in the selected firms. The study’s findings showed that both monetary and non-monetary incentive management strategies have significant impact on employee performance among telecom-munication firms in Kaduna metropolis. Based on the finding of the study, it was recommended that telecommunication firms continually review existing monetary and non-monetary incentive management strategies and design new incentive programs in order to encourage employee to perform better than their current performance level.